Evaluation of User Experience Information Systems Using Heuristic Evaluation (Case Study of STMIK Amik Riau Student Portal) - Heru Satria Surya; Benino Giordiola Millenio; Junadhi Junadhi; Silvyana Dwi Putri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
The academic information system is an important system to supports lecture activities. Is used by almost all elements in the university, both students, lecturers, staff and leaders. This research uses Heuristic Evaluation as an inference method to assess the components of learnability, efficiency, memorability, errors, and satisfaction. for various cases, such as designing academic and corporate websites with reference to these problems, it is necessary to evaluate the usability of STMIK Amik Riau information system. STMIK Amik Riau implements an integrated information system to support fast and real-time information management processes of STMIK Amik Riau information system includes various services such as E-KRS, E-KTM, E-EDOM, and other information. The aim is to identify problems related to the usability of the website. The data collection method in this research was carried out using questionnaire, containing a list of questions distributed via google form to respondents, its about 100 students of STMIK Amik Riau. Based on the analysis conducted using the Heuristic Evaluation method, the evaluation results of STMIK Amik Riau web portal have met the usability criteria with an average of 78.71915% where P > 60% and provides user satisfaction in accessing STMIK Amik Riau web portal. STMIK Amik Riau's web interface design is quite good. These results are based on the results of Likert scale score which states that the respondents agree.